Hubungan Komunikasi Interpersonal Kepala Sekolah, Komitmen dan Motivasi Kerja Guru Dengan Kinerja Guru SMPN Kecamatan Pelaihari Kabupaten Tanah Laut - Nopiyana, Nopiyana; Aslamiah, Aslamiah; Rizalie, Ahmad Muhyani (LP. Ma'arif Janggan Magetan, 2024)
The purpose of the study is to analyze the relationship between principals' interpersonal communication, work commitment, and work motivation with teacher performance at SMPN Pelaihari District, Tanah Laut Regency. This research is a correlational research with a descriptive-quantitative method. The research population are all teachers at SMPN Pelaihari District, Tanah Laut Regency as many as 147 people with a sample of 107 respondents taken by random sampling technique.The data collection uses questionnaire instruments and data analysis uses descriptive analysis, classical assumption test, multiple linear regression analysis and path analysis. The results showed that there was a relationship between: (1) interpersonal communication between the principal and teacher performance of 0.076, (2) work commitment with teacher performance of 0.181, (3) work motivation and teacher performance of 0.848, (4) Principal interpersonal communication with work commitment of 0.264, (5) Principal interpersonal communication with work motivation of 0.092, (6) Principal interpersonal communication through work commitment with teacher performance of 0.048, (7) Principal interpersonal communication through work motivation with teacher performance of 0.078. Based on the results of the determination coefficient test, it shows that the R Square value of the teacher performance variable is 0.334. The conclusion of this study is that the variables of interpersonal communication of principals, work commitment and work motivation affect the teacher performance by 33.4% while the remaining 66.6% is explained by other factors. Meanwhile, the R Square value of the work commitment variable is 0.346. This means that the variable of interpersonal communication of school principals is affected by work commitment by 34.6% and the rest are influenced by other factors, and interpersonal communication of school principals is affected by work motivation by 8.4% while the rest are explained by other factors outside the study.